MEMINIMALKAN KESALAHAN KONSEP PECAHAN MELALUI PEMBELAJARAN PENEMUAN TERBIMBING DENGAN GESTURE PRODUKTIF PADA SISWA SMP - Anton Prayitno; Dewi Tri Wulandari (Universitas Islam Malang, 2015)
Not easy to bring the students are able to understand the concept and meaning of fractions so we need a change in the way teaching is done by teachers because of possible knowledge is still limited so that the teacher always used the same way of time. In anticipation of this problem it is necessary to look for a formula appropriate learning so as to improve the ability to solve mathematical problems, especially in fractions. Teachers should continue to develop and implement a variety of ways variance so that students interested and excited in participating in math class one through guided discovery methods. From the above data shows that mistakes students in concepts and problem solving 13%, this means that the mistakes made by the students at the time of surgery to learn fractions and solving problems can be minimized by guided discovery learning. Guided discovery learning, which is examined in this study is to present the information by observing the shape of object manipulation, making conjectures, explain, and evaluate